2022
DOI: 10.1038/s41586-022-04490-x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Ni2+-dependent guanidine hydrolase in bacteria

Abstract: Nitrogen availability is a growth-limiting factor in many habitats 1 , and the global nitrogen cycle involves prokaryotes and eukaryotes competing for this precious resource. Only some bacteria and archaea can fix elementary nitrogen; all other organisms depend on the assimilation of mineral or organic nitrogen. The nitrogenrich compound guanidine occurs widely in nature 2-4 , but its utilization is impeded by pronounced resonance stabilization 5 , and enzymes catalysing hydrolysis of free guanidine have not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…However, kinetic constants in this range do not allow to draw conclusions about a potential physiological relevance. For example, we recently reported that despite its relatively high K M the guanidine hydrolase GdmH allowed Synechocystis to utilize guanidine as sole nitrogen source 8 . The analysis of further substrates that are not known to occur in humans indicated that the activity of GDAH strictly depends on a negatively charged functionality opposite to the guanidine group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, kinetic constants in this range do not allow to draw conclusions about a potential physiological relevance. For example, we recently reported that despite its relatively high K M the guanidine hydrolase GdmH allowed Synechocystis to utilize guanidine as sole nitrogen source 8 . The analysis of further substrates that are not known to occur in humans indicated that the activity of GDAH strictly depends on a negatively charged functionality opposite to the guanidine group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted before that AGMAT activity has never been demonstrated conclusively and it was speculated by others that so-far unidentified co-factors might be necessary for its activity 7 . For the recently discovered guanidine hydrolase, also a member of the ureohydrolase family, we showed that its activity depends on the chaperone-mediated insertion of Ni 2+ rather than Mn 2+ into the active site 8 . It is conceivable that isolated or recombinant AGMAT similarly lacks essential factors for its activity.…”
Section: Introductionmentioning
confidence: 98%
“…But the molecular players have only begun to emerge since 2017, beginning with the discovery of riboswitch-controlled operons dedicated to Gdm + metabolism and transport ( 45 ). Four unrelated classes of Gdm + riboswitches have been identified ( 45 , 47 , 48 , 49 , 50 ), along with three distinct enzymatic pathways for utilizing Gdm + as a nitrogen source ( 51 , 52 , 53 , 54 ), including as a sole nitrogen source by some bacteria ( 53 , 55 ). The bacteria that do not consume Gdm + —about half of those with Gdm + riboswitches—instead produce and export endogenous Gdm + , likely as a metabolic waste product ( 5 , 45 ).…”
Section: Guanidinium Exporters (Gdx)mentioning
confidence: 99%
“…The riboswitches bind Gdm + with K D values between ∼60 to 200 μM ( 45 , 47 , 48 , 49 ) to upregulate expression of the associated transporters and enzymes. These proteins have somewhat higher K m values for Gdm + , between ∼200 μM −1 mM ( 4 , 45 , 51 , 53 ), suggesting that Gdm + accumulation becomes toxic to cells and must be mitigated within this range.…”
Section: Guanidinium Exporters (Gdx)mentioning
confidence: 99%
“…[17][18][19][20][21] Moreover, selective degradation pathways exist to utilize guanidine as nitrogen sources. 17,[22][23][24] Following the clarification of guanidine degradation, we are currently investigating biotic sources of guanidine and close derivatives. The present work describes the first specific canavanine degradation pathway.…”
Section: Introductionmentioning
confidence: 99%